Katie up and down the hall : the true story of how one dog turned five neighbors into a family - Plaskin, Glenn (New York : Center Street, 2010)
"The heartwarming true story of how one special cocker spaniel turned four strangers into family"--Provided by publisher.
A journalist tells the story of his dog Katie, whose curiosity led him to befriend five neighbors in his Manhattan high rise, with whom he formed a makeshift family and weathered bad health, accidents, cold New York winters, and the terrors of 9/11.
Keywords: Plaskin, Glenn; Plaskin, Glenn; Cocker spaniels -- New York (State) -- New York -- Biography; Human-animal relationships -- New York (State) -- New York; Neighbors -- New York (State) -- New York -- Biography; Strangers -- New York (State) -- New York -- Biography; Families -- New York (State) -- New York; Cocker spaniels -- New York (N.Y.) -- Biography; Battery Park City (New York, N.Y.) -- Biography; New York (N.Y.) -- Biography; Battery Park City (New York, N.Y.) -- Social life and customs; New York (N.Y.) -- Social life and customs; Battery Park City (New York, N.Y.) -- Biography; New York (N.Y.) -- Biography; Battery Park City (New York, N.Y.) -- Social life and customs; New York (N.Y.) -- Social life and customs; Biographies